Rekonstruktion onkologischer Defekte im Becken-Perinealbereich – Bericht zum Konsensus-Workshop im Rahmen der 44. Jahrestagung der DAM 2023 in Bern, CH - Kappos, Elisabeth A.; Wendelspiess, Séverin R.; Stoffel, Julia; Djedovic, Gabriel; Rieger, Ulrich M.; Bannasch, Holger; Fritsche, Elmar; Constantinescu, Mihai; Andric, Mihailo; Croner, Roland S.; Schmidt, Volker J.; Plock, Jan A.; et al. (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2024)
The surgical-oncological treatment of pelvic and perineal malignancies is associated with a high complication rate and morbidity for patients. Modern multimodal treatment modalities, such as neoadjuvant radio-chemotherapy for anal or rectal cancer, increase the long-term survival rate while reducing the risk of local recurrence. Simultaneously, the increasing surgical radicality and higher oncological safety with wide resection margins is inevitably associated with larger and, due to radiation, more complex tissue defects in the perineal and sacral parts of the pelvic floor. Therefore, the plastic-surgical reconstruction of complex pelvic-perineal defects following oncological resection remains challenging. The reconstructive armamentarium, and thus the treatment of such defects, is broad and ranges from local, regional and muscle-based flaps to microvascular and perforator-based procedures. While the use of flaps is associated with a significant, well-documented reduction in postoperative complications compared to primary closure, there is still a lack of reliable data directly comparing the postoperative results of different reconstructive approaches. Additionaly, the current data shows that the quality of life of these patients is rarely recorded in a standardised manner. In a consensus workshop at the 44 th annual meeting of the German-speaking Association for Microsurgery on the topic of Reconstruction of oncological defects in the pelvic-perineal area, the current literature was discussed and recommendations for the reconstruction of complex defects in this area were developed. The aim of this workshop was to identify knowledge gaps and establish an expert consensus to ensure and continuously improve the quality of reconstruction in this challenging area. In addition, the importance of the patient-reported outcome measures in pelvic reconstruction was highlighted, and the commitment to its widespread use in the era of value-based healthcare was affirmed.
CRIS-Team Scopus Importer:2024-08-23
Keywords: musculocutaneous flap; patient-reported outcome measures; perforator flap; perineal reconstruction; quality of life